1994
DOI: 10.1515/znc-1994-3-415
|View full text |Cite
|
Sign up to set email alerts
|

c , T-Dependence of the Self Diffusion in Concentrated Aqueous Sucrose Solutions

Abstract: The self diffusion coefficients D of the water molecules and of sucrose have been deter mined by the pulsed field gradient NMR technique over a wide range of temperatures and concentrations (cmax: 70% w/w sue.). All temperature dependencies can be fitted to a VogelTammann-Fulcher equation. The isothermic concentration dependence of D for the sucrose is given by a simple exponential concentration dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…The self-diffusion coefficient of sucrose in aqueous bulk water is 2.7 × 10 −10 for a 10% solution and 0.23 × 10 −10 m 2 s −1 for a concentration of 50% w/w. 27 The confinement effect of the micropores is obvious. Table 1 Characterization of the Y-zeolites by the volume of micropores V micro and mesopores V meso (3-150 nm), the external surface S ext , and the water in the pores ω o in suspension.…”
Section: Rate Of Adsorptionmentioning
confidence: 99%
“…The self-diffusion coefficient of sucrose in aqueous bulk water is 2.7 × 10 −10 for a 10% solution and 0.23 × 10 −10 m 2 s −1 for a concentration of 50% w/w. 27 The confinement effect of the micropores is obvious. Table 1 Characterization of the Y-zeolites by the volume of micropores V micro and mesopores V meso (3-150 nm), the external surface S ext , and the water in the pores ω o in suspension.…”
Section: Rate Of Adsorptionmentioning
confidence: 99%
“…In this range of sugar concentrations, the ideal glass transition temperatures in the VTF equation, T 0 , for water are almost constant and similar to that of neat water. 17,25 This is approximately in the range of carbohydrate concentrations over which Rampp et al found a dramatic increase in the ratio of water to carbohydrate translational diffusivity with falling temperature using 13 C and proton NMR. 19 In addition, Champion et al showed a decoupling between translational diffusion and viscosity in concentrated sucrose solutions near the glass transition temperature T g using the fluorescence recovery after the photobleaching method.…”
Section: Introductionmentioning
confidence: 83%
“…Because of the importance of water in the chemical and physical degradation processes in formulations containing, primarily, proteins, carbohydrates, and water, a considerable amount of experimental work has been done to study water dynamics and structure in carbohydrate-water systems as a function of carbohydrate concentration and temperature. [17][18][19][20][21][22][23][24][25][26][27][28] One of the interesting observations from these previous studies is the dynamical decoupling between water and carbohydrates. The NMR work of Girlich and Lüdemann showed that the rotational dynamics of water, described by a Vogel-Tammann-Fulcher ͑VTF͒ equation, becomes almost concentration independent at sucrose concentrations greater than 60 wt %.…”
Section: Introductionmentioning
confidence: 99%
“…175 An interesting situation is found in aqueous sugar solutions in which rotational diffusion of water molecules becomes very free at high sugar concentrations ͑and seems as if it is unaware of the impending glass transition͒, while translational diffusion continues to be coupled to that of the sugar molecules. 176 These systems deserve much more study.…”
Section: C5 Mobile Water Molecules In Biomaterialsmentioning
confidence: 99%